Psychopathology of Young Terrorist Offenders, and the Interaction With Ideology and Grievances - Duits, Nils; Alberda, Daphne L.; Kempes, Maaike (Frontiers in Psychiatry, 2022)
Psychopathology might be a risk factor for terrorist offending as it is for violent offending. Therefore, we examined the prevalence of psychopathology in young and adult Jihadist terrorist offenders on the basis of primary source judicial information and forensic mental health reports with the European Database of convicted Terrorist offenders (EDT). We hypothesised that psychopathology might be associated with ideological risk factors, and that these associations might be different for young and adult terrorist offenders. Therefore, we examined whether and to what extent psychopathology is related to a violent ideology, to grievances and anger about perceived injustice. We investigated whether this differs among 120 adult and 46 juvenile terrorist offenders. We found that most adult and young Jihadist terrorist offenders with a forensic mental health report had psychopathological problems. Most frequently found were symptoms and traits of intellectual disability disorders, depressive disorders, psychotic/schizophrenic disorders, substance use disorders, and personality disorders. Most frequently found clinically relevant personality traits were problems with relationships, poor regulation of aggression, feelings of anger, and paranoid feelings. We found some first indications for a positive association between psychopathology and grievances and anger about perceived injustice. In the young terrorist offenders with depressive symptoms, grievances about perceived injustice were more often present than in young terrorist offenders without these symptoms. In adult terrorist offenders it was found that grievances about perceived injustice and the anger were related to cluster B personality traits. In addition, in both young and adult terrorist offenders expressed grievances about perceived injustice were related to problems with relationships. Further research into psychopathology in terrorist offenders seems necessary with larger groups of adolescents and adults in relation to ideological, personal and contextual risk factors and how these factors relate to different terrorist acts. This may lead to more knowledge about engagement into terrorism and possible disengagement from terrorism. It may also lead to the inclusion of psychopathology into violent extremism risk assessment tools.